NOTE ON ORGANIC COMPOSITION OF MUSCLE OF SOME EDIBLE FRESHWATER ANIMALS - Janakiram, B; Venkateswarlu, Y; Reddy, G Rajarami; Babu, K Sasira (Indian Journal of Fisheries, 2011)
High protein and lipid levels were noticed in the muscle of prawn, fishand frog, while the carbohydrate, free fatty acid and glycogen levels were highin frog and snail